Abnormal changes of bone metabolism markers with age in children with cerebral palsy - Xing, Wen; Liang, Lin; Dong, Na; Chen, Liang; Liu, Zhizhong (Frontiers in Pediatrics, 2023)
Cerebral palsy (CP) is a broad range of diseases with permanent and nonprogressive motor impairments, carrying a high cost for both the individual and the society. The characteristics of low bone mineral density and high risk of fractures suggest that bone metabolism disorders are present in CP. This study aims to investigate the association between indicators of bone metabolism and children with CP. A total of 139 children (75 children with CP and 64 healthy controls) were included in this cross-sectional study. Participants were divided into three age groups (0-2 years, 2.1-4 years, and 4.1-7 years). All children with CP were diagnosed according to clinical criteria and furtherly divided into clinical subtypes. The levels of total procollagen type I N-terminal propeptide (TPINP), N-MID osteocalcin (OC), beta-crosslaps (β-CTX), 25-hydroxyvitamin D (25-OHD) and parathyroid hormone (PTH) in the serum were measured with corresponding detection kits according to the manufacturer’s instructions. Serum levels of TPINP and 25-OHD were lower with older age, whereas β-CTX and PTH were higher with older age. In the CP group, TPINP (age 0- 2 years and 2.1- 4 years) and OC (age 2.1- 4 years) levels were higher, while β-CTX (age 2.1- 4 years and 4.1- 7 years) and PTH (age 2.1- 4 years) values were lower than the control group. In addition, there were no statistically significant differences in the levels of these indicators among the CP subgroups with different clinical characteristics. Our study shows that bone turnover markers, indicators of bone metabolism, in children with CP differ significantly from healthy controls. The indicators we studied changed with age, and they did not correlate with disease severity.